Architecture et société néolithique L'unité et la variance de la maison danubienne - Coudart, Anick (Documents d'archéologie française, 1998)
Domestic architecture is a means of examining the social structure of Neolithic groups in Europe from 5500 BC to 4500 BC Indeed. a house is built as much to order the social milieu as to dominate the physical environment. The Danubian house was first laid out according to strict cultural norms. This « uniformity » reflects a relatively « egalitarian » society, and a common conceptual System. However, numerous variations occurred. Apparently influenced by the type of relations between a site and its neighbours, this variability enabled individuals to react and ad on the System, but also contributed to the break-up of the Bandkeramik culture, and its replacement by new regional entities.